MEMAHAMI ADAPTASI PENDUDUK TERHADAP PERUBAHAN IKLIM UNTUK PEMENUHAN KEBUTUHAN AIR BERSIH DI PULAU-PULAU KECIL BELITUNG DAN BINTAN - Laksmi Rachmawati (Jurnal Kependudukan Indonesia, 2015)
Freshwater is an essential need for human being thus a sufficient supply of it it is required. Naturally, small islands are vulnerable. The occurence of climate change the vulnerability of these islands increase. Changes on temperature and precipitation can alter the hydrological cycle and will directly affect the water supply in small islands. This paper examines various adaptation efforts implemented by local population and government in small islands situated in Belitung and Bintan. Using quantitative method (survey to 400 respondents) and qualitative method (interview and focus group discussion),Â  the research found that the adaptation has already taken place. The responsive/reactive and anticipatory adaptation are managed by government and local people who live in these small islands. Some of the adaptation actions are widening water storage, buying, searching for new water resources, desalination of salt water, rain water harvesting and improvement of water distribution. In addition, local mangrove management in Selat Nasik acts as adaptation functions Â for barriers of salt water intrusion. However, water governance has not been prioritized although it is proven to be necessary to support adaptive capacity for fresh water fulfillmentÂ